Turbidimetria in-line na quantificação do tamanho de partícula de misturas poliméricas na extrusão - Bernardo, Felipe Oliveira Campos (Universidade Federal de São Carlos, 2017)
The morphology of mixtures and polymeric compounds is usually evaluated by off-line characterization methods, which require time for sample preparation and analysis of results. In-line rheo-optical characterization techniques during extrusion involve the quantification of the attenuation of an incident light beam caused by changes in the phase morphology and/or orientation of the polymer chains under flow. Processing conditions, including temperature, flow and pressure outputs are the variables that define the rheological behavior. This project has as main objective a particle size’s evaluation of a second polymer phase of polypropylene (PP) and polyethylene (PE) in polystyrene (PS) by the quantification of incident light attenuation via turbidimetry. The optical device used was bench-tested using standard samples for ceramic particles by light scattering, and for organic dyes by colorimetry, which were prepared in such a way that their parameter (second phase concentration, size of the dispersed particle or dispersed particle type) was changed in a known manner. The systematized study of the samples and the device’s validation were allowed. The analyzes were performed in real time by the pulse addition system during the melt blending process in a W&P ZSK 30 extruder coupled to an instrumented slit die while maintaining the screw rotation and the extruder flow rate constant. During the extrusions, by varying the concentration of the added pulses, different contributions of turbidity collected were obtained. Thus, the particle sizes for the polypropylene and polyethylene pulses were calculated, and such results showed the validity of the particle size analysis system developed, since, for the polymer particles added to the flow, the obtained values of average particle size were satisfactory, with consistent values according to the available literature.
In-line turbidimetry in the quantification of the particle size of polymeric mixtures in extrusion
Keywords: Detector óptico in-line; Espalhamento de luz; Colorimetria; Turbidimetria; Tamanho de partícula; Extrusão; In-line optical detector; Light scattering; Colorimetry; Turbidimetry; Particle size; Polymer extrusion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS